Influence of SiCp volume percentage on AA6063/SiCp MMC extrusion process: An experimental, theoretical and simulation analysis - Veerasundaram Jayaseelan; Kani Kalaichelvan; Nallamuthu Ramasamy; Murugesan Seeman (International Journal of Lightweight Materials and Manufacture, 2023)
Composites have been the most prominent incipient materials in a variety of industries over the past decades. The present work mainly investigates the influence of the SiC particulate (SiCp) weight percentage on AA6063/SiCp metal matrix composites extrusion and, it has been evaluated in extruded MMC billets for enhancing the billet quality. Graphite lubricants are used to decrease the friction between the die and the billet surface. Subsequently, the friction factor is theoretically determined and experimentally validated. It was concluded that SiCp concentration is the predominant factor influencing the extrusion load and friction factor. As a result, the extrusion load was increased with an increase in SiCp percentage. Furthermore, the experimental results were compared and validated by simulation analysis. The extruded billet surfaces were exhibited by a scanning electron microscope.